The Hyperreality of Accountability: A Critical Review of Regional Financial Reporting and Audit Practices in Indonesia - Mirna Amirya; Wiwied Tuhu Prasetyanto (Universitas Pendidikan Ganesha, 2026)
This study examines the phenomenon of hyperreal simulacra in the accountability of regional financial reporting in Indonesia. Using a critical literature review combined with qualitative document analysis informed by critical discourse analysis, this study explores how the practice of accountability presented in regional financial reports creates an illusion of transparency and accountability that does not actually reflect reality. The study draws upon Jean Baudrillard's theoretical framework to demonstrate that accountability in regional financial reporting and audit practice is frequently presented in a hyperreal manner. This presentation prioritizes normative formalities over an accurate reflection of financial conditions. The study's findings indicate that the simulacra of hyperreality in the accountability of regional financial management creates a misleading perception of the effectiveness of public financial management, a pattern reflected in recent Indonesian evidence in which unqualified audit opinions (WTP) coexist with persistent budgetary inefficiency and corruption (Abdullah et al., 2026; Sutaryo et al., 2023). This study contributes to the critical accounting literature by challenging the myth of accountability that has taken shape within the discourse of regional financial bureaucracy in Indonesia.